A study on construction and demolition wastes from buildings in Seberang Perai - Asaari, F.A.H.; Halim, H. Bt A.; Isa, M.H. (2004)
Construction and demolition (C&D) waste is defined as solid, bulky, largely inert waste resulting from the construction, renovation or demolition of buildings structures. As a whole, C&D wastes are considered to be composed of inert materials that will not leach into the groundwater. Even though C&D waste present a lower risk to human health and the environment compared to municipal solid waste, the bulky waste definitely consume a lot of space at landfills. C&D waste will increase from time to time in proportion to the development of a town and country. Thus, the necessity of finding appropriate solution to C&D waste destination must be clear. Hence, a study on the C&D waste generated has been conducted aiming to establish data on material composition, cost of handling and disposal, and the extent of waste recovery and type of disposal. A survey of 30 construction and demolition projects throughout the Seberang Perai area was made between August 2001 and January 2003. In addition, in order to get the representative data of C&D waste, public and private authorities were interviewed, and field study at Pulau Burung Sanitary Landfill was carried out.